Environmental protection in the exploitation and use of space resources. Issue 1 (September 2020) - Xu, Fengna
Abstract: Space resources activities are per se ultra-hazardous activities, which may be harmful to both outer space and the Earth environment. At the dawn of space mining, however, predominant in space mining missions is wealth and technology perspective. Environmental protection, has not been an important consideration. The principle of sustainable development and the new ecocentric approach could help to make a correct balance between protecting environment and promoting industrial development. But many obstacles of environmental protection do exist, such as inadequacies of the current space law, difficulties in practice, ethical dilemma in planetary protection. Thus, for promoting sustainable exploitation and use of space resources, this article suggests some solutions, including: 1) strengthening the legal regime; 2) promoting international cooperation; and 3) developing the appropriate ethic.